A STUDY OF THE SOCIAL INEQUALITY AND ITS EFFECTS ON INDIAN SOCIETY - Lokmani (International Journal of Multidisciplinary Research and Studies, 2021)
Exclusion is a consequence of social inequality. Commonly referred to as "social inequality," this phenomenon describes patterns of uneven access to social resources. It's a varied path to money, power, and status for various people. Inequality may exist in society based on factors such as gender, race, age, ethnicity, religion, and even kinship. Hegemony is a means by which inequality may be maintained over prolonged periods of time. The dominance of culture by one particular cultural group over another results in the exaltation of some cultural ideas, values, and practises at the expense of those of other cultures. This phenomenon is known as hegemony. Marx and Engels claimed that the true foundation of social and political disparity was property, and that because primitive cultures did not have private property, there was no state and no class or inequality in such societies. In communities that are organised according to ranks and strata, inequality has developed into a pervasive and enduring characteristic. The practise of the caste system in India is an example of a social stratification system in which racial or cultural disparities serve as the primary criteria for assigning social position. Membership in a caste is predetermined at birth and is not subject to change; castes have names and are territorially demarcated. Caste is a rigorous system of occupationally specialised, interdependent groups that has remained a key social institution in India. Caste is also known as the social stratification system. The caste system has always been one of the most prominent aspects of Hindu civilizations; yet, Muslim and Sikh groups have also preserved some aspects of the caste system, despite diverging philosophically and practically from Hindu practises and beliefs. The purity and contamination traditions that were used to organise political, economic, and ceremonial life are what are employed to rank the various castes.